2020
DOI: 10.3390/nano10030464
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light-Excited Room Temperature Phosphorescent Carbon Dots

Abstract: Carbon dots (CDs) with a room temperature phosphorescent (RTP) feature have attracted considerable interest in recent years due to their fundamental importance and promising applications. However, the reported matrix-free RTP CDs only show short-wavelength (green to yellow) emissions and have to be triggered by ultraviolet (UV) light (below 400 nm), limiting their applications in certain fields. Herein, visible-light-excited matrix-free RTP CDs (named AA-CDs) with a long-wavelength (orange) emission are report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 65 publications
0
32
0
Order By: Relevance
“…AA-CDs were prepared according to the previous work [29]. Typically, 2.0 mL of ammonia solution was added in 8 mL DI water, and then 1500 mg of L-aspartic acid (AA) was slowly added into this solution with stirring, and the precursor was completely dissolved by ultrasonic treatment for 15 min.…”
Section: Preparation Of Aa-cdsmentioning
confidence: 99%
See 1 more Smart Citation
“…AA-CDs were prepared according to the previous work [29]. Typically, 2.0 mL of ammonia solution was added in 8 mL DI water, and then 1500 mg of L-aspartic acid (AA) was slowly added into this solution with stirring, and the precursor was completely dissolved by ultrasonic treatment for 15 min.…”
Section: Preparation Of Aa-cdsmentioning
confidence: 99%
“…In both of the above cases, hydrogen bonding interactions between the emissive units of CDs and matrices/CDs' frameworks usually play a critical role to stabilize the excited triplet states and so as to activate their afterglows [21,22,25,26]. Although afterglow emission wavelengths from CDs-based materials have been successfully regulated from green to red region [27][28][29][30][31], NIR afterglow from CDs has not yet been reported so far, not to mention the NIR-containing dual-/multi-mode afterglows.…”
Section: Introductionmentioning
confidence: 99%
“…More interestingly, green and orange afterglow luminescence was observed from the same CDs@MS upon the excitation at wavelengths of 365 and 395 nm, respectively (Figure 8(a)) [80]. This mechanism can also be used to explain the excitation-dependent RTP of self-protective N-doped and N,P-codoped CDs [76,92].…”
Section: Emerging Afterglow Luminescence Propertiesmentioning
confidence: 95%
“…For example, Qi et al recently showed that microwave-assisted heating (800 W, 2 min) of a mixture of phytic acid and triethylenetetramine led to the production of self-protective afterglow CDs as well, exhibiting a maximum emission band at 535 nm with a long average lifetime up to 750 ms [96]. In a recent work by Hu et al [92], microwave-assisted heating of L-aspartic acid in the presence of ammonia was elucidated to be useful for preparing CDs with a unique orange afterglow luminescence (585 nm) with an average lifetime of 240.8 ms under excitation at 420 nm (Figure 7(i)). This finding suggests that the color output of the afterglow luminescence of CDs is likely to be manipulated by proper selection of the combination of CD precursors.…”
Section: Self-protective Activationmentioning
confidence: 99%
See 1 more Smart Citation